Photoisomerization mechanisms from trans, trans-1, 4-diphenyl-1, 3-butadiene: CASSCF on-the-fly trajectory surface hopping dynamic simulations. Issue 13 (11th March 2016) - Zheng, Xiaolei; Zhai, Gaohong; Gao, Wanqing; Lei, Yibo; Yu, Le; Zhu, Chaoyuan
Abstract : Photoisomerization mechanisms including two reactive pathways, one bond twist (OBT) and bicycle pedal (BP), and two non-reactive pathways, single bond torsion (SBT) and reverse torsion (RT). Abstract : We have employed the SA2-CAS(4, 4)/6-31G ab initio method together with an on-the-fly global-switching trajectory surface hopping algorithm to simulate photoisomerization reaction dynamics from reactant trans, trans -1, 4-diphenyl-1, 3-butadiene (DPB) to products cis, trans -DPB and cis, cis -DPB. This topic has been extensively studied experimentally and the present theoretical study is the first to simulate DPB photoisomerization reaction dynamics as far as we know. With total 600 sampling trajectories, 300 actively contribute to isomerization reaction via two conical intersections between the electronic ground and the first excited states. Simulated quantum yields of photoisomerization to cis, trans -DPB and cis, cis -DPB are 0.09 and 0.045, which are in good agreement with the experimental values of 0.07–0.25 and 0.02, respectively. The lifetime of the first excited state is estimated as 702 fs. The present simulation has shown two reactive photoisomerization mechanisms, namely one bond twist (OBT) and bicycle pedal (BP), and two non-reactive photoisomerization mechanisms, namely single bond torsion (SBT) and reverse torsion (RT) with respect to the central backbone CC bonds. We believe that the present theoretical work can benefit the experiments on photoisomerization of DPB derivates.